The Impact of Ethnomathematics Application on Mathematics Learning Achievement in Fourth Grade at SD Negeri 02 Bekonang - Ariani, Ardian Virgina; Suswandari, Meidawati (Universitas Ma'arif Lampung, 2024)
This study aims to investigate the impact of implementing ethnomathematics on mathematics learning outcomes among fourth-grade students at SD Negeri 02 Bekonang. The research employs a quantitative method with an experimental approach, involving a population of 44 students from classes IV (A) and IV (B). The students were divided into two groups: the experimental class, which applied ethnomathematical concepts through the traditional game engklek, and the control class, which learned without incorporating ethnomathematical concepts. The findings indicate that the experimental class achieved higher post-test scores compared to the control class. The average post-test score for the experimental class was 64.55, while the control class scored 51.82. The t-test analysis yielded a significance value of 0.037 < 0.05, demonstrating a significant influence of ethnomathematics on students' mathematics performance. The ethnomathematical approach, which integrates cultural elements into learning, has proven to be an effective strategy in mathematics education. This approach not only enhances students’ conceptual understanding but also makes learning more engaging and meaningful. In this study, the engklek game was used as a learning medium to introduce the concept of geometric shapes, allowing students to grasp the material more easily through direct experience. Therefore, this approach is recommended for mathematics instruction in elementary schools to foster student engagement and comprehension. This study also encourages teachers to be more creative in developing concrete and contextually relevant teaching methods, ensuring that mathematics is no longer perceived as a daunting subject.